2012
DOI: 10.1002/ibd.21738
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 5 deficiency protects from wasting disease in a T cell transfer colitis model in T cell receptor-β-deficient mice

Abstract: TLR5 expression on T cells is not required for induction of or protection from T cell-dependent colitis. Expression of TLR5 in non-T cells has a pathogenic role, since TLR5 deficiency in recipient mice protects against weight loss induced by WT T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Although our data are supported by a recent report on a protective role for TLR5 defi ciency for colitis development in a T cell transfer model [54], another study reported, in contrast, a potentiating effect of the TLR5 agonist fl agellin on induction, expansion and suppressive activity of Foxp3 + Tregs [28,52]. While differing compositions of commensal enteric communities between laboratories might explain these contrasting results, our data clearly show that microbiota-driven proliferation of conventional CD4 + T cells and Foxp3 + Tregs can occur in the absence of TLR-signaling.…”
Section: Discussionsupporting
confidence: 89%
“…Although our data are supported by a recent report on a protective role for TLR5 defi ciency for colitis development in a T cell transfer model [54], another study reported, in contrast, a potentiating effect of the TLR5 agonist fl agellin on induction, expansion and suppressive activity of Foxp3 + Tregs [28,52]. While differing compositions of commensal enteric communities between laboratories might explain these contrasting results, our data clearly show that microbiota-driven proliferation of conventional CD4 + T cells and Foxp3 + Tregs can occur in the absence of TLR-signaling.…”
Section: Discussionsupporting
confidence: 89%
“…Lamina propria mononuclear cells (LPMC) were isolated as previously described (28). Briefly, colons and ceca were collected, washed, and placed in a shaking incubator at 37°C in RPMI 1640 containing 10% heatinactivated FCS and 5 mM EDTA.…”
Section: Methodsmentioning
confidence: 99%
“…CpG, a TLR9 ligand, has also been reported to undermine Treg induction as well as suppression in a MyD88‐dependent loss of Treg function . In contrast, TLR5 ligation with flagellin has been reported to enhance Foxp3 expression and Treg function , although another study found TLR5 −/− Tregs were functional in vivo and potential immune suppressive effects were originated on other cell types .…”
Section: Treg Stability Is Regulated By Numerous External Inputsmentioning
confidence: 99%